Potentials, Threats and Challenges in Managing Natural Heritage in the Penang National Park (KEMANUSIAAN The Asian Journal of Humanities, 2015)
Penang is one of the most developed and highly urbanised states in Malaysia with very little remaining forests. The Penang National Park (PNP) was gazetted in 2003 with only 1200 hectares. It is one of the smallest national parks in the world, but the park is rich in natural heritage such as pristine rainforest, rich biodiversity, white sandy beaches, crystal clear sea, clean rivers, a meromictic lake and a scenic natural environment. However, many threats to the PNP are identified, including encroachment from farming, tourism development, environmental pollution, over-collection of plants and animals, poaching, ineffective management, poor enforcement and the lack of stakeholders' involvement. The challenges in managing the PNP include addressing all the mentioned threats. Although not a straight forward and easy task, the threats can be reduced via a holistic and integrated management approach, careful planning and expert guidance, strict monitoring of development and enforcement, and active involvement of all stakeholders via empowerment. The park can also be developed into a nature education centre for students and used as a natural laboratory for research and data collection. On the whole, integrated environmental planning and management of the PNP with a focus on ecotourism will lead to sustainable development and ensure the park remains a lasting natural heritage area.